The Value of Long-Chain Fatty Acid Analysis, Randomly Amplified Polymorphic DNA and Electrophoretic Karyotyping for the Characterization of Wine Yeast Strains - van der Westhuizen, T.J.; Augustyn, O.P.H.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
Wine yeast strains of Saccharomyces had previously been classified into several different species or varieties. This classification system was based mainly on sugar fermentation and assimilation patterns. Subsequently, most of these species were reclassified as Saccharomyces cerevisiae. The assignment of the majority of wine yeast strains to a single species does, however, not imply that all stains of S. cerevisiae are equally suitable for wine fermentation. These physiological strains of S. cerevisiae differ significantly in their fermentation performance and their ability to contribute to the final bouquet and quality of the various types of wine and distillates. Therefore, to ensure strain authenticity, security and proper strain management, it is of cardinal importance to have reliable taxonomic techniques available to identify and characterize individual strains of commercial cultures. In this study, 18 commercial wine yeast strains were characterized in order to evaluate and compare three taxonomic techniques, namely long-chain fatty acid analysis, randomly amplified polymorphic DNA (RAPD) and electrophoretic karyotyping. As a single identification technique, electrophoretic karyotyping seems to be the most useful method for routine fingerprinting of wine yeast strains. However, we propose that the combined use of these three techniques provides the most reliable means of differentiating amongst commercial wine yeast strains.